Mortality after pediatric kidney transplantation in England – a population‐based cohort study. (18th October 2013) - Farrugia, Daniela; Cheshire, James; Mahboob, Sophia; Begaj, Irena; Khosla, Sajan; Ray, Daniel; Sharif, Adnan
Abstract The aim of this study was to explore mortality after pediatric kidney transplantation in England over the last decade. We used data from HES to select all kidney transplant procedures performed in England between April 2001 and March 2012. Data linkage analysis was performed with the ONS to identify all deaths occurring among this study cohort. Data for 1189 pediatric recipients were compared to 17 914 adult recipients (number of deaths, 33 vs. 2052, respectively, p < 0.001), with median follow‐up 4.4 yr (interquartile range 2.2–7.3 yr). There was no difference in mortality within the pediatric cohort; age 0–1 (n = 25, patient survival 100.0%), age 2–5 (n = 198, patient survival 96.0%), age 6–12 (n = 359, patient survival 97.5%), and age 13–18 (n = 607, patient survival 97.4%), respectively (p = 0.567). The most common causes of death were renal (n = 8, 24.2%), infection (n = 6, 18.2%), and malignancy (n = 5, 15.2%). All deaths from malignancy were secondary to PTLD. In a fully adjusted Cox regression model, only white ethnicity was significantly associated with risk of pediatric mortality post‐kidney transplantation (hazard ratio 2.7, 95% confidence interval [1.0–7.3], p = 0.047). To conclude, this population‐based cohort study confirms low mortality after pediatric kidney transplantation with short follow‐up.